Effect of Planting Time on Sheath Blight Disease of Rice in Bangladesh - Parveen, S; Bhuiwan, MR; Khan, MAI; Ali, MA (Bangladesh Rice Journal, 2019)
Sheath blight (ShB) caused by Rhizoctonia solani is one of the major disease of rice (Oryza sativa L.) in Bangladesh. Effect of planting time on ShB disease of BRRI dhan49 was observed at the experimental plots of Bangladesh Rice Research Institute, Gazipur. Two field experiments were conducted to develop management strategy for controlling ShB during T. Aman 2010-11 seasons. Four planting dates viz. 15 July, 30 July, 15 August and 30 August were imposed to record the effect of planting time on incidence and severity of ShB disease on BRRI dhan49. Significant differences on the Relative Lesion Height (RLH) among the treatments were observed during both 2010 and 2011 seasons. For both the seasons, the highest RLH was recorded in plots transplanted on 15 August (62.1% in 2010 and 61.2% in 2011) because of the remaining high temperature, rainfall and humidity and the lowest in plots transplanted on 30 July (19.4% for both). Similarly, the maximum severity score was recorded in 15 August transplanting (7) and the minimum in 30 July (1) respectively. Percent disease index (PDI) was also varied significantly among the treatments for both the seasons. During both the years, the maximum PDI was recorded in 15 August (76.5 and 75.2% respectively) and the minimum in 30 July transplanting (20.4 and 20.1 respectively). However, the highest number of filled grains panicle-1 was counted in 30 July (151), followed by15 July transplanting (145) during 2010. But, it was the highest in 30 July (141), followed by 15 August transplanting (136) during 2011. Again for both the seasons, the lowest filled grains panicle-1 was recorded in 30 August transplanting (116 and 127). Similarly for both the years, the maximum grain yield was observed in 30 July (6.29 and 5.82 t ha-1 respectively), followed by 15 July (5.67 and 5.17 t ha-1) and the lowest in 30 August transplanting (3.80 and 4.27 t ha-1 respectively). However, 1000 grain weight was 20 g in each date of transplanting during both the seasons. Finally, Integrated Disease Management (IDM) packages need to be developed by using appropriate planting time, cultural practices and fungicides to control ShB disease of rice. Bangladesh Rice j. 2018, 22(2): 55-62